2021
DOI: 10.1111/1541-4337.12762
|View full text |Cite
|
Sign up to set email alerts
|

Technological properties of chickpea (Cicer arietinum): Production of snacks and health benefits related to type‐2 diabetes

Abstract: Chickpea (Cicer arietinum) is one of the most consumed pulses worldwide (over 2.3 million tons enter the world market annually). Some chickpea components have shown, in preclinical and clinical studies, several health benefits, including antioxidant capacity, and antifungal, antibacterial, analgesic, anticancer, antiinflammatory, and hypocholesterolemic properties, as well as angiotensin I‐converting enzyme inhibition. In the United States, chickpea is consumed mostly in the form of hummus. However, the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 109 publications
0
13
0
1
Order By: Relevance
“…potassium, calcium, magnesium, iron and zinc) 1,2 . Several possible health benefits of the intake of chickpea in daily diet have been reported in the literature, including the positive impacts on type 2 diabetes, obesity, hypertension, cardiovascular diseases and colorectal cancer 1,3 …”
Section: Introductionmentioning
confidence: 99%
“…potassium, calcium, magnesium, iron and zinc) 1,2 . Several possible health benefits of the intake of chickpea in daily diet have been reported in the literature, including the positive impacts on type 2 diabetes, obesity, hypertension, cardiovascular diseases and colorectal cancer 1,3 …”
Section: Introductionmentioning
confidence: 99%
“…Yağcı, Altan, and Doğan (2020) also produced a wholesome extruded snack product using chickpea–yogurt-based blends, and the resulting snack contained high protein content and fiber with reduced beany flavor and antinutritional factors. Apart from this research, several studies incorporated pulse proteins into puffed extruded products and studied their physicochemical and sensory characteristics. …”
Section: Utilization Of Pulse Protein For Food Applicationsmentioning
confidence: 99%
“…Adiponectin is a hormone that prevents type two diabetes and atherosclerosis (Achari and Jain, 2017). A randomized cross-over clinical trial with diabetic patients (n = 32) served with a chickpea diet (substituting two servings of red meat) increased levels of adiponectin in all patients (Mirmiran et al, 2019;Acevedo Martinez et al, 2021). Additionally, a study with diabetic rats has demonstrated reduced blood glucose and triglyceride levels upon feeding 400 mg/kg of aqueous and methanol-based doses of chickpea diets (Yagi and Yagi, 2018).…”
Section: Fatty Acids and Human Health Benefitsmentioning
confidence: 99%